Digital Assets Regulation in Inheritance Law Reviewed from a Civil Law Perspective - Yudhi Patra; Rizki Tri Anugrah Bhakti; Dwi Afni Maileni; Agus Riyanto (Jurnal Cakrawala Hukum, 2026)
Rapid advancements in science and technology, propelled by globalization, have fundamentally reshaped life, facilitating cross-border information dissemination and electronic transactions. This transformation presents significant challenges for civil law, particularly in the realm of digital asset inheritance. This article analyzes how Indonesian civil law, based on principles found in the KUHPerdat), navigates the complexities of abstract digital assets, their volatile economic value, and platform terms that limit heir access. Employing a descriptive-analytical normative juridical research method with a literature review, this study identifies existing legal gaps and issues stemming from the absence of specific regulations for digital assets as inheritance objects. While digital assets can be categorized as intangible movable property inheritable under civil law, their application in customary inheritance law requires further exploration of local wisdom. As solutions, this research recommends comprehensive legal regulatory updates for digital assets, increased public digital literacy regarding inheritance planning, and robust collaboration among the government, legal institutions, and digital service providers. These steps are crucial to protecting heirs' rights, ensuring legal certainty, and preventing the loss or misuse of digital assets in an increasingly digitized era. Keywords: Digital Assets, Inheritance Law, Civil Law.